Petrography and reservoir quality controls in shallow transitional marine Cretaceous-Paleogene deposits in the Dahomey Basin, Nigeria. (February 2022) - Adamolekun, Olajide J.; Busch, Benjamin; Suess, Michael P.; Molenaar, Nicolaas; Hilgers, Christoph
Abstract: Upper Mesozoic and Early Cenozoic sedimentary rocks are of great significance to the petroleum geology of the Eastern Dahomey Basin as they are valuable prospects for hydrocarbon reservoirs. Diagenesis and reservoir quality (porosity and permeability) controls are deduced from core samples recovered from six shallow exploration wells in the onshore area of the Eastern Dahomey Basin using petrographic, petrophysical and mineralogical tools. The studied lithostratigraphic intervals consist of limestone, calcareous siliciclastic sandstone (Ewekoro and Araromi Formations), quartz arenite and clay-matrix supported sandstone (Afowo Formation) which were deposited within a shallow marine depositional environment. Siliciclastic samples of the Ewekoro Formation consist predominantly of calcareous sandstone and limestone, which are classified as packstone and wackestone. The porosity values in the sandstones range from 5 to 36% whereas permeability ranges from 0.006 to 109 mD. Ewekoro Limestone porosity ranges from 7 to 32% and permeability ranges from 0.003 to 13 mD. Samples of the Araromi Formation exhibit a porosity of 4 to 45% with permeability between <0.001 and 1764 mD in sandstones whereas a single limestone sample has 8% porosity and permeability of 0.03 mD. Porosity in quartz arenitic sandstones of the Afowo Formation ranges from 15 to 47% with permeability of 0.05 to >10, 000 mD, while in the clay-matrix supported sandstones, the values range from 18 to 42% and 0.05 to 5 mD for porosity and permeability, respectively. The main pore-occluding authigenic minerals are carbonate cements (Fe-dolomite, Fe-calcite, siderite and dolomite), iron oxide, kaolinite, and illite-smectite mixed layer clays. The best reservoir quality is observed in the quartz arenitic sandstones of the Araromi and Afowo Formations, except for the low permeability, clay-matrix supported sandstone facies. The most significant controlling factors in sandstones are clay mineral matrix contents and the presence of carbonate cements. Fe-calcite, Fe-dolomite and kaolinite formation occurs during early diagenesis in the studied lithologies and has helped to reduce the effect of compaction. The results of this study indicate fair to good reservoir quality in the shallow marine sedimentary rocks of the Eastern Dahomey Basin, which could be targeted in further exploration campaigns in the region. Highlights: Reservoir quality study of Cretaceous to Paleogene marine deposits Detrital clay matrix preserves porosity but deteriorates permeability Early diagenetic carbonate cementation preserves IGV High IGV samples have higher permeability at the same porosities as low IGV samples Dolomitic limestones contain high microporosity